(untitled) (Journal of Civil Engineering Researchers, 2025)
Concrete-filled steel tube (CFST) columns are widely used in high-rise buildings around the world due to their numerous structural advantages, including high load-bearing capacity, favorable inherent ductility, substantial energy absorption capabilities, and the elimination of the need for formwork. However, in Iran, these structures have not yet been widely implemented in practice, highlighting the need for further research in this area. Additionally, challenges such as buckling and local delamination between the concrete and steel under loading remain key issues for these columns. Research indicates that circular CFST columns provide the strongest confinement for concrete, whereas square CFST columns exhibit higher local buckling under loading. Furthermore, embedded steel profiles significantly enhance the overall performance of these columns. In this study, a finite element model of CFST columns with embedded cruciform profiles is validated using Abaqus software and subsequently analyzed parametrically. The objective of this study is to evaluate the seismic and axial performance of the "primary column cross-sections" and the "embedded steel profiles" with equivalent areas. The findings of this research demonstrate that filling the internal space of steel columns with concrete substantially improves axial and lateral performance, although it slightly reduces lateral ductility. Additionally, stress analysis reveals that the type of embedded steel profile directly influences the enhancement of load-bearing capacity and lateral performance. Results also show that square CFST columns outperform their circular counterparts in terms of axial strength and stiffness, though they exhibit lower axial ductility. Moreover, the results indicate that embedded profiles with concentrated mass at the center (central profiles) significantly enhance axial performance, whereas those with mass concentrated along the perimeter (peripheral profiles) exhibit the lowest axial performance but the highest lateral performance criteria.